Reproductive success, parental care, and nest morphology of Manacus candei (Passeriformes, Pipridae) - Riera Dinarés, Sara; Rojas, Emmanuel; Mata-Núñez, Melanie; Sandoval, Luis (Revista de Biología Tropical, 2025)
Introduction: With the destruction of natural habitats due to human activities (i.e., agriculture and urbanization), species face new challenges to survive and reproduce. Some of the new challenges include predation rate and food resources, a lack of nesting substrates and the type of nesting materials (i.e., natural and artificial). Since predation is reported as the primary cause of nest loss in the tropics, studying its impact, along with nest morphology, in modified environments is essential to understanding its effects on species inhabiting these habitats. Objective: This study evaluates nesting success and predation for the white-necked manakin (Manacus candei) in a fragmented area near the Tirimbina Biological Reserve (Costa Rica). Methods: Between 2015 and 2019, 66 nests were monitored, 59 of which were used to calculate the daily survival rates (DSR) of the nests using the MARK program. The other seven nests were only monitored by camera traps to identify predators and observe the mother’s behavior. We measured 20 nests and compared the variation on morphology. Results: The results suggest that DSR nests did not vary between months or years, and the constant survival model was the most suitable with an average of 95% and a real survival of 11.6%. This species suffered a 64% nest failure, mostly due to predation. In total, four nest predators were identified, three avian and a domestic cat. Additionally, two species of birds were observed stealing nesting material. Nests were very similar in morphology with a coefficient of variation below 38% in their measurements. Conclusion: These results suggest that the non-natural garden zone could provide a safe nesting place for M. candei, since it could be acting on the predator community.